1997
DOI: 10.1089/scd.1.1997.6.235
|View full text |Cite
|
Sign up to set email alerts
|

Positive Selection and Transplantation of Peripheral CD34+ Progenitor Cells: Feasibility and Purging Efficacy in Pediatric Patients with Neuroblastoma

Abstract: Peripheral stem cells were mobilized and collected in 20 children with stage 4 neuroblastoma. A total of 37 leukaphereses were performed in the 20 patients. The mean number of collected cells was 5.6 +/- 2.4 x 10(8)/kg (range 1.9-10.5), and the number of collected CD34+ progenitors was 6.1 +/- 6.3 x 10(6)/kg (range 0.75-21.7). CD34-positive selection was performed using the CellPro method. Of the adsorbed cells, 42 +/- 20% (range 4.3-76.6) stained positively for CD34, and the number of positively selected CD34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
4

Year Published

1998
1998
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 19 publications
3
31
0
4
Order By: Relevance
“…Other investigators have reported lower incidences of tumor cell contamination in PBSC harvests (0-50%) and bone marrow harvests (30-50%) from pediatric patients with solid tumors. 15,18,[30][31][32][33][34][35][36] There may be several reasons for this difference. First, the patient populations may be different.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported lower incidences of tumor cell contamination in PBSC harvests (0-50%) and bone marrow harvests (30-50%) from pediatric patients with solid tumors. 15,18,[30][31][32][33][34][35][36] There may be several reasons for this difference. First, the patient populations may be different.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Preclinical studies have suggested several clinical applications of highly purified CD34 ϩ cells, including tumour cell purging. Enrichment of CD34 ϩ cells has been proven to deplete tumour cells from autografts, [13][14][15][16][17][18] and is necessary for ex vivo expansion of progenitor cells. Furthermore, highly purified CD34 ϩ cells are essential for optimal cytokine-mediated expansion and differentiation in short-term culture.…”
mentioning
confidence: 99%
“…However, we have noted first a persistent decrease in CD4 + lymphocyte levels and a high incidence of serious and life-threatening late complications (two patients had EBV-associated lymphoproliferation, six children had severe VZV infection and six severe septic shock events occurred after completion of hematopoietic reconstitution); second, a delayed platelet recovery which is longer than in historical series. 78,79 Other published experience of PB CD34 + cell selection in children 43,69 confirms the feasibility of this technique and a successful short-term engraftment of PB CD34 + cells. However, in children as well as in adults' questions concerning the use of ex vivo modified PBPCs remain open: to define categories of patients for whom selection is beneficial and to balance the advantages and disadvantages of grafting selected cells.…”
Section: Collection In the Smallest Of Childrenmentioning
confidence: 65%
“…[43][44][45][46][47][48] Few teams use peripheral venous access together with a central catheter installed at diagnosis. 12,49 Only when it is deemed impossible to ensure adequate blood flow with peripheral veins is a CVC installed under local anesthesia and sedation.…”
Section: Venous Access and Related Complicationsmentioning
confidence: 99%
See 1 more Smart Citation